Konsep Pola Makan menurut Al-Qur'an dalam Kajian Tafsir Tematik - Muhammad Naufal Nuruddin Salim; Dadan Rusmana (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2022)
Diet is one of the determining factors in human health, but in fact the Muslim community in Indonesia still does not understand the concept of eating patterns in the Qur'an. Many people still eat excessively, it is proven that Indonesia is the 2nd largest producer of food waste in the world. There are also those who consume forbidden foods or drinks such as liquor and drugs and like to consume less nutritious foods. Al-Qur'an and Hadith as the main sources of Islamic teachings have taught a good diet for physical and spiritual health. This research is a qualitative research with library research method that examines how the concept of eating patterns in the Qur'an. The data collected were analyzed using an interpretive approach with the maudhui interpretation method. The results of the study indicate that a quality healthy life can be obtained, among others, by protecting a diet that is not excessive, eating nutritious food, according to what the body needs, and eating halal thoyyiban which has been prescribed by Islam.